Nación, república y Constitución: La Liga Patriótica Argentina y su Congreso General de Territorios Nacionales - Galucci, Lisandro (Jahrbuch für Geschichte Lateinamerikas, 2017)
The purpose of this article is to analyze the discourses performed by the participants of the General Congress of National Territories, organized in 1927 by the Liga Patriótica Argentina, a nationalist association of notorious presence in the political life of the Argentinian Republic during the 1920’s. The congress was the Liga’s response to some of the problems its members found not only in the political situation of the republican institutions, but also in the specific case of the Territories, units that had no political autonomy and that were subject to the authority of the federal government. The Territories represented almost half of the Argentinian territory, and were seen as spaces inexcusably abandoned by the federal governments. Thus, the Liga embraced the self-assigned mission of ‘argentinizing’ those spaces and their populations. Among other aspects, this involved debating the institutional status of the Territories, namely their recognition as new provinces. Although some Territories had reached the legal conditions required, that transformation had not yet occurred by 1927. However, establishing a position on that subject was not an easy issue for the Liga. As this article proposes to demonstrate, the difficulties the Liga had in defining its official position on the provincialization of Territories can be explained as a result of the ways in which its members understood the key concepts of Nation, Republic and Constitution, so as the relations between them.
Keywords: Nationalism; Interwar; Argentina; National Territories; Patagonia